Clause-level constructions in Tagalog - Basaca, Casiana C. 1930- (s.n.], 1969)
This is a descriptive analysis of the various Tagalog clause types with the aim of helping Tagalog learners gain a better understanding of Tagalog structures and to help teachers predict learning problems of students and prepare linguistically sound instructional materials. The tagmemic method is used for analysis.